Analisis Model Epidemi SEIR Menggunakan Metode Runge-Kutta Orde 4 pada Penyebaran COVID-19 di Indonesia - Rahmadhani, Anis Putri; Kusumastuti, Ari; Juhari, Juhari (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2023)
This study discusses the analysis of the Susceptible-Exposed-Infected-Recovered (SEIR) epidemic model using the fourth-order Runge-Kutta method on the spread of COVID-19 in Indonesia by taking into account the factors limiting community interaction and the percentage of vaccination as model parameters. The purpose of this study was to determine the application of the Susceptible–Exposed–Infected–Recovered (SEIR) model using the fourth-order Runge-Kutta method in dealing with COVID-19 in Indonesia. The steps in analyzing the model are to determine the stability of the model that produces local asymptotic stability, then carry out the implementation as well as simulation using the fourth-order Runge-Kuta method in dealing with COVID-19 in Indonesia. The calculation results show the effect of limiting community interaction and vaccination in reducing cases of COVID-19 infection. Where, when limiting public interaction, the number of cases of COVID-19 infection is lower than before the restrictions on community interaction were carried out, and the higher percentage of vaccinations also resulted in more sloping infection cases. This study provides information that if restrictions on community interaction continue to be carried out by continuing to increase the percentage of vaccinations, it is estimated that the daily graph of positive cases of COVID-19 will be increasingly sloping and close to zero. Thus, the addition of new cases will decrease and it is hoped that the COVID-19 pandemic will end soon.